A comparative evaluation of the effect of liners on the shear bond strength of veneered zirconia block: An in vitro study - Pooja Yadav; Nupur Dabas; Sumit Singh Phukela; Puja Malhotra; Shefali Drall; Pankaj Kumar Ritwal (The Journal of Indian Prosthodontic Society, 2019)
Aim: This study aims to evaluate the effect of lithium disilicate glass–ceramic liner, silicon dioxide based liner, and glass–ceramic interlayer on the shear bond strength (SBS) of a commercially available veneered zirconia block and to study fractographic behavior of the samples using universal testing machine, scanning electron microscope (SEM). Setting and Design: In vivo – comparative study. Materials and Methods: 60 samples were fabricated from VITA (vita zahnfabrik. Bad sackingen, Germany) zirconia discs. Samples were divided into 4 groups with 15 samples each. First is the control group, second is lithium disilicate glass–ceramic liner group, third is silicon dioxide based liner, and fourth is glass–ceramic interlayer group. SBS of samples was recorded using universal testing machine. Samples were further analyzed for fractographic behavior using SEM. Statistical Analysis Used: One Way ANOVA test, and Chi-Square test. Results: The intergroup comparison of mean SBS (Mpa) was done using the post hoc Bonferroni test. The mean SBS (Mpa) was significantly more among lithium disilicate and glass–ceramic interlayer groups in comparison to silicon dioxide-based liner group. Fractographic analysis was done using the Chi-square test. Conclusion: It was concluded that maximum SBS was obtained for lithium disilicate liner. Maximum adhesive failures were found with lithium disilicate liner, and silicon dioxide-based liner group showed cohesive failures.